Excitation Spectra of Cubic Perovskite Titanates - Phuc, Le Hong; Hien, Nguyen Quang; Nguyen-Truong, Hieu T.; Le, Hung M. (Communications in Physics, 2022)
We calculate excitation spectra of cubic perovskites ATiO3 (A = Ca, Sr, Ba, Pb). The calculations are performed within the time-dependent density functional theory, including local field effects. The theoretical calculations show that the perovskites have a plasmon mode at around 12 eV, which is not observed in experiments.